Collaborations. - Eipeldauer, Heike; Thalmair, Franz; mumok - Museum moderner Kunst Stiftung Ludwig Wien (Köln : Verlag der Buchhandlung Walther und Franz König, 2022)
Marina Abramović and Ulay ; Anna and Bernhard Blume ; Valie Export ; Rimma Gerlovina and Valerij Gerlovin ; Gilbert & George ; Natalia LL ; Art & Language ; Bruce Conner ; Richard Hamilton and Dieter Roth ; Alison Knowles ; Louise Lawler ; Stephen Prina ; Robert Watts ; Heimo Zobernig ; Secession ; Wiener Gruppe ; Otto Muehl ; Günter Brus ; Die Damen ; Jörg Schlick ; Hubert Schmalix ; Daniel Spoerri ; Franz West ; Oswald Wiener ; Joseph Beuys, Bazon Brock, Rolf Jahrling, Ute Klophaus, Charlotte Moorman , Nam June Paik, Eckart Rahn, Tomas Schmit, Wolf Vostell ; George Brecht ; George Maciunas ; Johannes Cladders ; Peter Faecke ; Robert Filliou ; Kerstin von Gabain and Nino Sakandelidze ; Dan Graham ; Willem de Ridder ; Beau Geste Press ; Seth Siegelaub ; Manfred Grübl ; Thomas Struth ; Andy Warhol ; Leidy Churchman ; Ray Johnson ; On Kawara ; Lucy Lippard ; Ree Morton ; Nam June Paik ; Timm Ulrichs ; Martin Beck ; Chto Delat ; Clegg & Guttmann ; Phil Collins ; Andreas Gursky ; Sharon Lockhart ; Otto Neurath ; Petr Štembera ; Yoko Ono ; John Cage and Merce Cunningham ; John Lennon and Yoko Ono ; Christine and Irene Hohenbüchler ; Franz Erhard Walther ; Ant Farm ; Haus-Rucker-Co. ; IRWIN ; Friedrich Kiesler
Collaborations, mumok - Museum moderner Kunst Stiftung Ludwig Wien, Vienna, July 2 - November 6, 2022
boek